If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 78x = 52x + 13 Reorder the terms: 7 + 78x = 13 + 52x Solving 7 + 78x = 13 + 52x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52x' to each side of the equation. 7 + 78x + -52x = 13 + 52x + -52x Combine like terms: 78x + -52x = 26x 7 + 26x = 13 + 52x + -52x Combine like terms: 52x + -52x = 0 7 + 26x = 13 + 0 7 + 26x = 13 Add '-7' to each side of the equation. 7 + -7 + 26x = 13 + -7 Combine like terms: 7 + -7 = 0 0 + 26x = 13 + -7 26x = 13 + -7 Combine like terms: 13 + -7 = 6 26x = 6 Divide each side by '26'. x = 0.2307692308 Simplifying x = 0.2307692308
| 132=m+89 | | 8x+4x+y+3y=12x+4y | | 4(8v-7)=164 | | 3+(2*x)=15 | | 6(11-x)=42 | | 5/12x3 | | 103=5x+4(2x+3) | | (6x^2-9x+4)-(8x-12)= | | A=21(3.14)m^2 | | 2x+13=3x-22 | | (-8x^2y^8z^7)/(12x^4y^5z^7) | | -5(5+4x)=-85 | | -2x+2x=-6+12x | | s=40x-x^2 | | 90+x=189 | | 3+1(2x+2)=6x | | x+44+2x-5=180 | | z=a | | 5x=485 | | x-19=x+29 | | 5x+25=-25 | | 3x^7*4x^4= | | 25a^2-100=70 | | 4(x-11)/3=12 | | 4-3x=-4/3 | | 2x^2+8lnx=0 | | 3(4x-8)=12(3a+8) | | 4(x-11)/3 | | 54x=1026 | | fx=8x^2-2x | | (6x+24)+(17x-9)=180 | | 6(x+40)=270 |